Asset recovery policy strategy of corruption proceeds placed abroad within the perspective of the state as a victim - Sihite, M. Idris; Mustofa, Muhammad (Technium Social Sciences Journal, 2021)
This study aims to examine the policy for the recovery of assets resulting from corruption placed abroad with a descriptive-qualitative approach and using a methods case study. Based on the identification and interpretation of data with a policy framework criminal Hoefnagels (1969) and William N. Dunn's (2003) forecasting policy analysis. It was found that Indonesia needed to strengthen cooperation in the form of mutual legal assistance (MLA) and information on financial transactions with the country for which the assets were embezzled track, seize and freeze the assets of corruptors. The government needs a framework for new law in the form of an asset confiscation law that is supported by the availability of resources adequate human resources (HR) of law enforcers to facilitate the recovery process assets resulting from corruption abroad. The government also needs to reform the face of the bureaucracy and transparent, humanist, professional, and responsive to national law enforcement issues corruption. Indonesian political will to reciprocally provide assistance to other countries in the asset recovery process is highly recommended. The government also needs to reform the Asset Recovery Center (PPA) as an independent institution while strengthening the human resource capacity of the members.